Short stature/short limb skeletal dysplasia with severe combined immunodeficiency and bowing of the femora: report of two patients and review. - MacDermot, K D (1991)
We report two patients with severe combined immunodeficiency and short stature/short limb skeletal dysplasia. Case 1 presented at birth with rhizomelic shortening of the extremities and bowing of the femora. She developed clinical signs of severe combined immunodeficiency at 13 months and died at 21 months. Case 2 had severe prenatal shortening and bowing of the extremities and a small, malformed chest. Symptoms of severe combined immunodeficiency and severe failure to thrive developed soon after birth and she died at 5 months. The diagnosis of severe combined immunodeficiency in our patients was based on their clinical course and necropsy findings, supported in case 1 by the results of immune function tests. The results of investigation of immune function (immunoglobulins, lymphocyte subpopulations, lymphocyte function) are very variable in this syndrome as in other variants of severe combined immunodeficiency. Bone histopathology in both patients showed grossly irregular costochondral junctions, but normal transition of proliferating to hypertrophic chondrocytes. These cases belong to early lethal type 1 short limb skeletal dysplasia with severe combined immunodeficiency. Review of previously published cases with severe combined immunodeficiency and well documented skeletal findings show eight patients with prenatal onset of bowing and shortening of the extremities and metaphyseal abnormalities. These include two sib pairs concordant for the skeletal changes. In these cases, adenosine deaminase levels were not reported. An additional four published cases with associated adenosine deaminase deficiency had only mild metaphyseal abnormalities, but subsequently showed no linear growth.(ABSTRACT TRUNCATED AT 250 WORDS)